Decoding Neanderthals - Powell, Nick Clarke; Gibbon, Johanna Woolford; Harding, Ben (PBS Distribution, 2013)
Over 60,000 years ago, the first modern humans left their African homeland and entered Europe, then a bleak and inhospitable continent in the grip of the Ice Age. But when they arrived, they were not alone: the stocky, powerfully built Neanderthals had already been living there for hundreds of thousands of years. So what happened when the first modern humans encountered the Neanderthals? Did they make love or war?